RETRACTED: AI methods application for classifying stratigraphic layers of snow cover with Snow micro pen device - Frolov D.M.; Seliverstov Yu.G.; Koshurnikov A.V.; Gagarin V.E. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001